Beyond Aesthetics: A Femme Manifesto - Hoskin, Rhea Ashley; Hirschfeld, Katerina (Atlantis, 2018)
This creative piece pushes the reader to think beyond femininity's articulation as a source of oppression to, instead, consider how it can be reframed as a form of resistance.